Optimal Configuration of Intelligent Soft Switches in Active Distribution Networks Based on Locational Marginal Price - QIU Cheng; ZHAO Wanjian; LI Xincong; ZHANG Mingze; FEI Fei; PENG Haohua; ZHOU Jianqiao; SHI Gang; ZHANG Jianwen (Journal of Harbin University of Science and Technology)
With the implementation of the“ double carbon”target, the penetration rate of DG from intermittent distributed power sources in active distribution networks is increasing, which brings about increasingly prominent problems such as voltage overruns and network blockages. Intelligent soft switch SOPs can replace contact switches in the distribution network. During normal operation, SOPs can achieve real-time voltage regulation and tide control, provide fast fault isolation and power supply restoration, and improve the controllability of the distribution network. Due to the high configuration cost of SOPs, the problem of their siting and capacity setting becomes the core of the problem. In the paper, an optimal SOP configuration method based on locational marginal price (LMP) is proposed. Firstly, for the uncertainty of DG operation, a typical scenario is generated using a fuzzy clustering approach, and the optimal SOP access location is determined through a siting strategy based on improving the the distribution of locational marginal price in the system; on this basis, a two-layer model with the lowest annual operating cost of the system in the upper layer and the lowest system operating losses in the lower layer is established. The model is combined with the cone planning method to optimize the siting and solved. Finally, the feasibility of the SOP configuration scheme proposed in the paper is verified by using the improved IEEE33 the distribution of locational marginal price as an example. The results show that the method proposed in the paper can effectively improve the distribution of locational marginal price, reduce the comprehensive annual operating costs of the distribution network and improve the system operating economy.